Brain Lesions in Aging Zoo-Housed Naked Mole-Rats (Heterocephalus glaber). Issue 1 (January 2021) - Ward, Jerrold M.; Cartoceti, Andrew N.; Delaney, Martha A.
Naked mole-rats (NMRs) are common in the managed care of zoos and valuable models for aging research. Limited information on NMR neuropathology is available despite many studies regarding their aging physiology. Histologic sections of brain from 27 adult (5–27 years old) NMRs from 2 zoos were reviewed to determine presence or absence of lesions associated with advanced age in humans and other mammals. A majority (23/27; 85%) of NMR brains had cerebral cortical neuronal changes with rounded or angular neurons, cytoplasmic vacuoles containing pale yellow pigment, periodic acid–Schiff (PAS)-positive granules and green autofluorescence, compatible with lipofuscinosis. Less severe lesions were present in cerebellar Purkinje cells, medulla, and hippocampal neurons. The hypothalamic neuropil of all NMRs had scattered variably sized PAS-positive granules and 10 (37%) had larger round bodies consistent with corpora amylacea. The youngest NMRs, 5 to 7 years old, generally had minimal or no cerebrocortical lesions. Further studies will help understand brain aging in this long-lived species.